Insect parasitoids : a Canadian perspective on their use for biological control of forest insect pests - Smith, S.M. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1993)
An overview of biological control programs against forest insect pests is presented with emphasis on Canadian case histories. The work is examined in the context of conservation, introduction, and augmentation (environmental manipulation and inoculative and inundative release) of insect natural enemies, specifically parasitoids. Historically, studies have concentrated on introductions of exotic parasitoids for control of introduced pests where a number of successes have been recorded. More recent work has entailed inoculative and inundative releases of parasitoids against native pests in an attempt to establish new host-parasitoid relationships to reduce pest populations. These have had limited success and are still being explored by Canadian researchers. Current strategies for using natural enemies are inundative release of native species against native pests and conservation of native parasitoids through selective insecticide timing and forest manipulation. Future directions in biological control programs will include these approaches with increased emphasis on biotechnology and the genetic selection or manipulation of 'desired strains' for release. Continued ecological studies will be essential to ensure a more complete understanding of the interaction between these 'selected parasitoids' and the forest/tree parameters which will influence their success (tri-trophic interactions). These parameters, such as tree vigour (pest resistance), spatial distribution and diversity, will also be targeted for selection to improve the effect of insect natural enemies in the forest environment.